Socio-economic impact of riverbank failure at Kg. Pohon Celagi in Pasir Mas, Kelantan, Malaysia - Too, See Kay Leng; Mokhtar Jaafar; Frankie Marcus Ata; Mohd Ridhuan Mohd Jamil (Penerbit Universiti Kebangsaan Malaysia, 2023)
Riverbank failure is a geological phenomenon that occurs when the soil or rock comprising the bank of a river collapses, leading to the rapid erosion of land and the formation of large cracks and sinkholes. While it is a natural occurrence, riverbank failure can have severe consequences for nearby communities and the environment. A massive riverbank failure occurred along the Kelantan River in Kampung Pohon Celagi, Pasir Mas, Kelantan, Malaysia. In this study, the affected area of the riverbank failure was determined and the effects of the bank failure on the village socio-economics and community were investigated. This study utilized interview methods and field observations to collect data and information. The study shows that 0.58 km3 land in the village was affected by the riverbank failure. The local authorities designated the 50-m range from the riverside as the red zone where most houses and buildings collapsed with the riverbank movement, and the parameters were 51–100 m is the high-risk area, 101–150 m is moderate, and ≥ 151 m upwards is low risk area, respectively, from the riverbank. The affected communities were required to move to safer areas and leave their properties to be demolished or failure with the riverbank. Socioeconomically, businesses around the disaster area were affected as they were prohibited from operating in the high-risk area. Overall, the disaster resulted in the local communities losing their property and experiencing depression. As a result, it is expected that all stakeholders will work together to develop a solution that ensures the well-being and safety of the community from riverbank failure.